Conférence: «Culture de mort / Culture de vie: Idéologie du genre en Colombie» - Anctil Avoine, Priscyll (2020)
Conférence intitulée « ''Culture de mort'' / ''Culture de vie'' : ''Idéologie du genre'' en Colombie » donnée par Priscyll Anctil Avoine, doctorante en science politique avec concentration en études féministes à l’Université du Québec à Montréal, dans le cadre du panel « Antiféminismes en Amérique latine : les cas du Brésil et de la Colombie » organisé le 21 février 2020 à l'UQAM par le Réseau québécois en études féministes (RéQEF), en collaboration avec l'Institut de recherches et d'études féministes de l'UQAM (IREF), le Réseau d'études latino-américaines de Montréal (RÉLAM) le Réseau d'études latino-américaines de Montréal (RÉLAM) et le Groupe de recherche en études féministes en science politique de l'UQAM (GREF).
Keywords: LGBTQIA2+; amérique latine; amériques; antiféminisme; approches et analyses; avortement; colombie; discours dominant; genre; identités LGBTQIA2+; justice reproductive; privilèges; régions géographiques; systèmes d'oppressions; thématiques

Save Yourself - Esposito, Cameron (Grand Central Publishing, 2020)
This "hilarious and honest" bestselling memoir from a rising comedy star tackles issues of gender, sexuality, feminism, and the Catholic childhood that prepared her for a career as an outspoken lesbian comedian (Abby Wambach).Cameron Esposito wanted to be a priest and ended up a stand-up comic. Now she would like to tell the whole queer as hell story. Her story. Not the sidebar to a straight person's rebirth-she doesn't give a makeover or plan a wedding or get a couple back together. This isn't a queer tragedy. She doesn't die at the end of this book, having finally decided to kiss the girl. It's the sexy, honest, bumpy, and triumphant dyke's tale her younger, wasn't-allowed-to-watch-Ellen self needed to read. Because there was a long time when she thought she wouldn't make it. Not as a comic, but as a human. SAVE YOURSELF is full of funny and insightful recollections about everything from coming out (at a Catholic college where sexual orientation wasn't in the nondiscrimination policy) to how joining the circus can help you become a better comic (so much nudity) to accepting yourself for who you are-even if you're, say, a bowl cut-sporting, bespectacled, gender-nonconforming child with an eye patch (which Cameron was). Packed with heart, humor, and cringeworthy stories anyone who has gone through puberty, fallen in love, started a career, or had period sex in Rome can relate to, Cameron's memoir is for that timid, fenced-in kid in all of us-and the fearless stand-up yearning to break free.
Keywords: amériques; approches et analyses; corps; humour; identités LGBTQIA2+; personnes lesbiennes; privilèges; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; travail; états-unis

Intersectionality in feminist and queer movements: Confronting privileges - Evans, Elizabeth; Lépinard, Éléonore (Routledge, 2020)
Examining the ways in which feminist and queer activists confront privilege through the use of intersectionality, this edited collection presents empirical case studies from around the world to consider how intersectionality has been taken up (or indeed contested) by activists in order to expose and resist privilege. The volume sets out three key ways in which intersectionality operates within feminist and queer movements: it is used as a collective identity, as a strategy for forming coalitions, and as a repertoire for inclusivity. The case studies presented in this book then evaluate the extent to which some, or all, of these types of intersectional activism are used to confront manifestations of privilege. Drawing upon a wide range of cases from across time and space, this volume explores the difficulties with which activists often grapple when it comes to translating the desire for intersectionality into a praxis which confronts privilege. Addressing inter-related and politically relevant questions concerning how we apply and theorise intersectionality in our studies of feminist and queer movements, this timely edited collection will be of interest to students and scholars from across the social sciences and humanities with an interest in gender and feminism, LGBT+ and queer studies, and social movement studies.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; intersectionnalité; militance; outils; ouvrages de références; privilèges; queer; ressource en ligne; systèmes d'oppressions; thématiques